2023
DOI: 10.1002/anie.202219340
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Temperature Bias through Reliable Temperature Determination in Gas‐Solid Photothermal Catalytic Reactions

Abstract: Enormous advances in photothermal catalysis have been made over the years, whereas the temperature assessment still remains controversial in the majority of photothermal catalytic systems. Herein, we methodically uncovered the phenomenon of temperature determination bias arising from prominent temperature differences in gas-solid photothermal catalytic systems, which extensively existed yet has been overlooked in most relevant cases. To avoid the interference of temperature bias, we developed a universal proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…While the results presented here may be considered “negative,” they highlight a few important findings. First, the results demonstrate the effectiveness (and necessity) of using thermocouples in the catalyst bed, at least for small catalyst bed volumes of densely packed particles, to account for light-induced metal nanoparticle heating. ,, Second, comparison of the results presented here to other reports of photocatalysis by metal nanoparticles, where thermocouples were used in the catalyst bed, lends confidence to previous conclusions of inherent photochemical responses for various catalytic systems. Thermocouples have been proposed as less reliable than temperature-sensitive IR cameras to measure catalyst temperatures accurately .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…While the results presented here may be considered “negative,” they highlight a few important findings. First, the results demonstrate the effectiveness (and necessity) of using thermocouples in the catalyst bed, at least for small catalyst bed volumes of densely packed particles, to account for light-induced metal nanoparticle heating. ,, Second, comparison of the results presented here to other reports of photocatalysis by metal nanoparticles, where thermocouples were used in the catalyst bed, lends confidence to previous conclusions of inherent photochemical responses for various catalytic systems. Thermocouples have been proposed as less reliable than temperature-sensitive IR cameras to measure catalyst temperatures accurately .…”
Section: Discussionsupporting
confidence: 75%
“…9 Thus, rigorous assessment of temperature measurement methods (like IR imaging or the use of thermocouples) is essential, and it has been demonstrated that the measured temperature values can strongly differ depending on the method used. 27,28 Further studies are needed that demonstrate reference "cases" where the influence of photon fluxes can be explained entirely through equilibrium heating. 29 Benchmarking setups, measurements, and approaches against such reactions will allow proper assignments of photochemical effects.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalytic performance was evaluated in a fix-bed reactor using a thin layer of Rh-NP/SiO x -NS composite particles (∼0.7 mm in thickness, ∼7 mg in mass) on a platinum mesh, which can minimize the photothermal effect. 32 The loose packing of the particles favored the isotropic and uniform mass transport of gas flow and heat transfer, ensuring fast dissipation of heat generated from light absorption ( i.e. , photothermal effect) to eliminate significant temperature deviation from the set temperature and temperature gradient in the thin catalyst layer (ESI,† Part II and Table S1).…”
Section: Resultsmentioning
confidence: 99%